(untitled) (ENVIRONMENT. TECHNOLOGY. RESOURCES. Proceedings of the International Scientific and Practical Conference, 2024)
In 2018, the first group of teachers and students from Vasil Levski National University conducted experiments on laser marking in Rezekne Academy Of Technology, Latvia. Since then, joint research has been increasing every year and better results have been achieved not only in the field of laser technologies, but also in other areas of joint interest. A pilot study group is even being formed in a master's program in laser technology. As a result, the interest in laser technologies and in Latvia at Vasil Levski National University increased significantly. Research has been done on the impact of the exchange between the two institutions on the learners and their motivation to learn.